Value change through information exchange in human–machine interaction. (1st June 2022) - Friedrich, Orsolya; Gerlek, Selin; Seifert, Johanna; Schleidgen, Sebastian
Abstract : An essential component of human–machine interaction (HMI) is the information exchanged between humans and machines to achieve specific effects in the world or in the interacting machines and/or humans. However, such information exchange in HMI may also shape the beliefs, norms and values of involved humans. Thus, ultimately, it may shape not only individual values, but also societal ones. This article describes some lines of development in HMI, where significant value changes are already emerging. For this purpose, we introduce the general notion of eValuation, which serves as a starting point for elaborating three specific forms of value change, namely deValuation, reValuation and xValuation. We explain these along with examples of self-tracking practices and the use of social robots.